PENENTUAN KONDUKTIVITAS LISTRIK DAN KAJIAN KUALITAS AIR SUNGAI SIAK MENGGUNAKAN METODE JEMBATAN WHEATSTONE - Alan Perdana Aritonang; Riad Syech; Walfred Tambunan (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been done on the determination of the electrical conductivity and water quality of Siak River water using a Wheatstone bridge method in the location around the rubber factory of PT. RICRY. The research was begun by taking samples of the Siak river water were taken on five points which have been determined at a distance of 10 meters from PT. RICRY when was low and high tide. Based on the length data of wire L1 and L1, it could be determined the value of electrical resistance, resistivity and electrical conductivity. The result showed that the value of highest electrical conductivity of the river water when the sea water was at high tide was 58,513 . 10-6 (Ωm)-1, while the electrical conductivity of the river water at low tide was 41,879 . 10-6 (Ωm)-1. A decent water for consumption has an electrical conductivity of (300 -500).106(Ωm)-1(Mailinda, U. 2011). Based on that standard electrical conductivity, Siak river water in the research location when the sea water high tide and low tide are not worthy to be consumed because of too small value compared to the standard value of electrical conductivity .